2012
DOI: 10.1007/s10936-012-9219-1
|View full text |Cite
|
Sign up to set email alerts
|

Interference and Facilitation in Spoken Word Production: Effects of Morphologically and Semantically Related Context Stimuli on Picture Naming

Abstract: We report two picture-word interference experiments investigating conceptual and lexical activation, and response selection, in speaking. We varied stimulus onset asynchrony to investigate potential fine-grained activation and competition effects. Morphologically related existing and pseudoword adjectives, as well as associatively related adjectives, served as context stimuli in Experiment 1. In Experiment 2, we focused on semantic interference by using morphologically related and unrelated subordinates of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…However, most of them also provide evidence for morpheme based lexical representations (e.g. Bö lte, Dohmes, & Zwitserlood, 2012;Lü ttmann, Zwitserlood, Bö hl, & Bö lte, 2011; but see Janssen, Bi, & Caramazza, 2008). Similarly to the comprehension data, compound noun retrieval in production also seems to be unaffected by semantic transparency (Bö lte et al, 2012;Gumnior, Bö lte, & Zwitserlood, 2006;Lü ttmann et al, 2011;Roelofs & Baayen, 2002).…”
mentioning
confidence: 71%
See 2 more Smart Citations
“…However, most of them also provide evidence for morpheme based lexical representations (e.g. Bö lte, Dohmes, & Zwitserlood, 2012;Lü ttmann, Zwitserlood, Bö hl, & Bö lte, 2011; but see Janssen, Bi, & Caramazza, 2008). Similarly to the comprehension data, compound noun retrieval in production also seems to be unaffected by semantic transparency (Bö lte et al, 2012;Gumnior, Bö lte, & Zwitserlood, 2006;Lü ttmann et al, 2011;Roelofs & Baayen, 2002).…”
mentioning
confidence: 71%
“…Bö lte, Dohmes, & Zwitserlood, 2012;Lü ttmann, Zwitserlood, Bö hl, & Bö lte, 2011; but see Janssen, Bi, & Caramazza, 2008). Similarly to the comprehension data, compound noun retrieval in production also seems to be unaffected by semantic transparency (Bö lte et al, 2012;Gumnior, Bö lte, & Zwitserlood, 2006;Lü ttmann et al, 2011;Roelofs & Baayen, 2002). Using the pictureÁ wordÁinterference paradigm, Lü ttmann and colleagues (2011; see also Zwitserlood, Bölte, & Dohmes, 2002) found that priming with opaque and transparent compound distractors was equally effective and lowered picture naming latencies when compared to unrelated distractor compounds.…”
mentioning
confidence: 83%
See 1 more Smart Citation
“…Even if the typical and often described result is interference, the PWIP can just as much induce semantic facilitation, yet under certain experimental conditions. Semantic facilitation in the PWIP has been obtained with a large panel of semantically related words: coordinates (Finkbeiner and Caramazza, 2006 ), subordinates (Costa et al, 2003 ), superordinates (Vitkovitch and Tyrrell, 1999 ; Damian and Abdel Rahman, 2003 ), associates not being coordinates (e.g., milk-cow; Alario et al, 2000 ; Costa et al, 2005 ; Sailor et al, 2009 ; de Zubicaray et al, 2013 ; Damian and Spalek, 2014 ; Sailor and Brooks, 2014 ), related adjectives (e.g., chilly-ice; Bölte et al, 2013 ) and related verbs (e.g., sit-chair; Mahon et al, 2007 ). More crucially, some PWIP studies demonstrated that the exact same set of materials used in slighlty different experimental settings can shift the polarity of the effect from interference to facilitation.…”
Section: Introductionmentioning
confidence: 99%
“…A major aim of contemporary psycholinguistic research is to understand and model the cognitive processes that speakers use to produce words. A very popular tool to investigate these processes and their time course is the picture‐word interference paradigm (e.g., Briggs & Underwood, ; Lupker, ; Rayner & Posnansky, , for early studies; see Bölte, Dohmes, & Zwitserlood, ; Bürki, Sadat, Dubarry, & Alario, ; Damian & Spalek, ; Porcaro, Medaglia, & Krott, ; Roelofs & Piai, ; Roelofs, Piai, Garrido Rodriguez, & Chwilla, , for more recent work). In this paradigm, participants are asked to name a picture and to ignore a distractor, presented either in the auditory or in the visual modality.…”
Section: Introductionmentioning
confidence: 99%